Sources of error for periodontal probing measurements - Grossi, S G; Dunford, R G; Ho, A; Koch, G; Machtei, E E; Genco, R J (Journal of periodontal research, 1996)
This study determined the relative contribution to probing measurement reliability of several factors, compared with that of random error. Probing measurements were performed by examiners properly trained and calibrated. A total of 5771 pairs of replicate pocket depth (PD) and relative attachment level (RAL) measurements were performed with the Florida Probe. A total of 1488 replicate clinical attachment level (CAL) measurements were performed with the North Carolina 15 mm probe. In addition, longitudinal replicate measurements of RAL were performed at 0 and 12 months on 816 sites in 11 patients utilizing the Florida Probe 20 mm disk probe. Measurement reliability with the Florida Probe resulted in mean intraexaminer variances of 0.21 and 0.33, for PD and RAL, respectively (s.e.m. 0.46 mm for PD and 0.57 mm for RAL). Measurement reliability with the conventional probe resulted in mean intra-examiner variances of 0.19 for PD and 0.32 for CAL (s.e.m. 0.44 mm and 0.56 mm). Pocket depth contributed to = 5% of the variability of the intra-examiner variance with both probes with other contributing factors being the individual patient, tooth and site location. Mean intra-examiner reproducibility for duplicate RAL measurement performed at 0 and 12 months was 0.24 and 0.19, respectively (s.e.m. 0.49 mm and 0.43 mm). In conclusion, a mean intra-examiner variance of < or = 0.24 can be achieved for replicate measurements with both electronic and conventional probes for moderate and severe periodontitis patients. Individual examiner, individual patient and site location contribute up to 10% to the overall variance. Hence, the pattern of variability for intra-examiner variance of probing measurements performed with either electronic or conventional probes by trained and calibrated examiners is mostly random error.